2006
DOI: 10.1111/j.1445-5994.2006.01155.x
|View full text |Cite
|
Sign up to set email alerts
|

Screening for colorectal cancer by faecal occult blood test: why people choose to refuse

Abstract: To better understand the personal barriers that limit participation in faecal occult blood test (FOBT) screening for colorectal cancer, non-participants from a recent screening initiative were sent detailed questionnaires, defining their reasons for not participating, as well as how to make screening more attractive. The important barrier was procrastination. The type of FOBT kit offered influenced the reasons for not participating. Convenient FOBT and greater general practitioner involvement may be important … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
60
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(64 citation statements)
references
References 5 publications
4
60
0
Order By: Relevance
“…On the other hand, 77% of participants believed that CRC can be treated if diagnosed early, which is a good sign in helping to motivate people with implementing screening programs. This was consistent with other national and international studies [13,18,19,24].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…On the other hand, 77% of participants believed that CRC can be treated if diagnosed early, which is a good sign in helping to motivate people with implementing screening programs. This was consistent with other national and international studies [13,18,19,24].…”
Section: Discussionsupporting
confidence: 93%
“…In order to create targeted messages and educational material aimed to booster participation in screening, it is required to understand the levels of knowledge, attitudes and beliefs of the target population [18]. Poor knowledge of CRC risk factors and the benefits of screening programs are potential barriers towards active participation in screening campaigns [19]. Previous researches suggested that the level of knowledge of CRC was poor both in developed and developing countries; with even lower levels of knowledge about the well-established screening tools and their benefits [17,20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Potential barriers, such as finding the test unpleasant or fear of the results, were overcome by a strong desire to know their CRC status, but a more ambivalent attitude resulted in procrastination, which was identified as the main reason for not completing the FIT. Previous research has also identified procrastination as a major barrier to CRC screening (Janz et al, 2007;McCaffery et al, 2001;Vernon, 1997;Worthley et al, 2006). This relationship between ambivalence and procrastination in CRC screening should be explored further.…”
Section: Discussionmentioning
confidence: 99%
“…In the general population, the main cited barriers to CRC screening are lack of knowledge (Berkowitz, Hawkins, Peipins, White, & Nadel, 2007), lack of trust in doctors (Lasser, Ayanian, Fletcher, & DelVicchio Good, 2008), lack of doctors' recommendation (Wardle et al, 2004), fatalistic views about cancer (Lasser et al, 2008), procrastination (Worthley, Cole, Esterman, Mehaffey, Roosa, Smith et al, 2006) and embarrassment (Rossi, Federici, Bartolozzi, Farchi, Borgia, & Guasticchi, 2005).…”
Section: Evidence For Barriers To Realised Accessmentioning
confidence: 99%